Światło zwycięskie, światło odrzucone. Motyw światła w Iz 1–39 - Popko, Łukasz (Verbum Vitae, 2016)
Any correct and in-depth interpretation of a metaphor necessarily presumes a reference to some definite context. The article presents a collection of texts from Isa 1–39 (2:5; 4:2-5; 5:20.30; 6:9-10; 9:5-6; 10:17; 26:19; 29:18; 30:26) where the motif of light is applied. Its various forms are inspired by the Ancient Near-Eastern cultures, which associate light especially with a divine sphere, king, victory and just rule. In Isa 1–39 light appears both in the eschatological contexts and in connection with the meaning of knowledge, especially knowledge of God. Thus the motif of light links these two fundamental contexts, not only enriching the interpretation of both but also suggesting a direct, causal relationship between knowing God and eschatological victory.